Metabolic Insights Into the Effects of Nutrient Stress on Lactobacillus plantarum B21 - Parlindungan, Elvina; May, Bee K.; Jones, Oliver A. H. (Frontiers in Molecular Biosciences, 2019)
Lactobacillus plantarum B21 is a strain of lactic acid bacteria first isolated from a fermented meat product from Vietnam. It is also a promising biopreservative with potential use in the food industry as it is a source of a novel bacteriocin (Plantacyclin B21AG) which has inhibitory effects against a wide range of species, including several pathogenic and spoilage strains. Nutrient stress is known to increase the survivability, storage stability and bacteriocin production capability of L. plantarum B21 during industrial processing. It is however, unknown what the underlying biochemical responses that control these abilities are. This study therefore investigates the metabolite profiles of L. plantarum B21 using NMR spectroscopy and GC-MS to further understand the biochemical responses of this strain to various stress events. Unstressed cells were found to use glucose as their primary energy source with high concentrations of metabolites involved in glycolysis and organic acid synthesis, such as lactic acid, acetic acid, propanoic acid, malic acid and 2-butenedioic acid being present in these cells. In contrast, large numbers of metabolites involved in amino acid metabolism including alanine, glutamic acid, aspartic acid, valine, proline and norleucine were upregulated in glucose stressed cells, indicating that they were using amino acids as their main source of energy. Differences in levels of fatty acids, particularly octadecenoic acid, tetracosanoic acid and 7-hexadecenoic acid were also observed between stressed and unstressed cells. The results from this study provide insight on the biochemical response of this bacterial strain to stresses commonly found during industrial processing.